1997
DOI: 10.1021/es960722j
|View full text |Cite
|
Sign up to set email alerts
|

Elution of Pyrene from Activated Carbon into an Aqueous System Containing Humic Acid

Abstract: The elution of pyrene (Pyr) into an aqueous solution containing humic acids (HAs) was investigated using activated carbon (AC) as an adsorbent of Pyr. The apparent water solubility of Pyr that adsorbed to the AC was increased by the presence of HAs. To quantitatively interpret the water solubility enhancement of Pyr in the presence of HAs, the partition coefficient of Pyr was evaluated using a micellelike partition model that took into account the partition of Pyr between water and the HA phase. The relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Such biomimetic catalysts have the potential to serve as clean remedial processes for the removal of organic pollutants in soils. In soil environments, humic acids (HAs) are ubiquitous and play important roles in the remediation of organic pollutants via a variety of interactions, including solubilization [5] and electron transfer [6]. However, HAs are heterogeneous compounds and their physicochemical properties vary with the type of soil.…”
Section: Introductionmentioning
confidence: 99%
“…Such biomimetic catalysts have the potential to serve as clean remedial processes for the removal of organic pollutants in soils. In soil environments, humic acids (HAs) are ubiquitous and play important roles in the remediation of organic pollutants via a variety of interactions, including solubilization [5] and electron transfer [6]. However, HAs are heterogeneous compounds and their physicochemical properties vary with the type of soil.…”
Section: Introductionmentioning
confidence: 99%
“…This experiment was conducted based on method reported in literature (Fukushima et al, 1997). The mixture of each PM (activated carbon, kaolinite, and ferrihydride) 1.0 g and 1.81 × 10 −3 mM DEHP in ethanol (100 mL) was stirred for 24 h. Subsequently, this mixture was filtered through a silica fiber filter (Advantec QR100), which can filtrate 99.9% of 0.3 μm particles (dioctyl phthalate).…”
Section: Desorption Experiments Of Dehp From Pm In the Presence Of Hamentioning
confidence: 99%
“…However, since the DEHP molecule is much smaller than the HA macromolecule, we can assume on the first approximation that the sorption behaviour of HA-DEHP on PM is similar to that of HA (Fukushima et al, 1997) …”
Section: Desorption Of Dehp From Pm In the Presence Of Hamentioning
confidence: 99%
“…On the one hand, humic substances are naturally occurring, surface active materials that have amphiphilic characteristics, thus giving them both hydrophilic and hydrophobic properties. Such functions of humic substances can serve as media for the sorption of hydrophobic organic contaminants, such as polycyclic aromatic hydrocarbons (Fukushima et al, 1997;Wang and Xing, 2005), polychlorinated dibenzo-p-dioxins (Yabuta et al, 2004;Tanaka et al, 2005;Fukushima et al, 2006) and chlorophenols (Robinson and Novak, 1994;Paolis and Kukkonen, 1997). In addition, it has been reported that the affinity of hydrophobic organic contaminants for clay minerals can be enhanced by complexation with humic substances (Terashima et al, 2003;He et al, 2006).…”
Section: Introductionmentioning
confidence: 99%